NÖROTROFİK FAKTÖRLERİN AĞRILI DİYABETİK NÖROPATİ ÜZERİNE ETKİLERİNİN İNCELENMESİ - KILINÇ, FARUK (Fırat Üniveristesi, 2009)
Diabetes mellitus, insülin etkisinin ya da insülin salgılanmasının veya her ikisinin bozukluğunun meydana getirdiği karbonhidrat, yağ ve protein metabolizmasında bozukluklara neden olan kronik hiperglisemi olarak tanımlanır.Bu çalışmada streptozosin (STZ) ile indüklenmiş diyabetik farelerde, nörotrofin?4 farklı dozlarının hot plate ağrı eşiği düzeylerine etkileri araştırıldı.Otuz beş adet 3 haftalık erkek fareler kullanıldı. STZ ile diyabet indüklenmiş farelerde indüksiyonu takiben (yaklaşık 4. hafta); diyabetik hayvanlar alt gruplara bölündü. Birinci grup sağlıklı kontrol grubu (n=15), ikinci grup diyabetik kontrol grubu (n=10), üçüncü grup düşük doz (0.3 mg/kg) recombinant human NT-4 uygulanacak grup (n=4) ve dördüncü grup yüksek doz (3mg/kg) recombinant human NT-4 uygulanacak grup (n=6) farelerden oluşturuldu.Sonuç olarak bu çalışmada STZ ile diyabet oluşturulan farelerde nörotrofik faktörlerin ağrılı DN üzerine etkilerini incelemek amacıyla hot plate testi uygulanmış olup çalışmanın önemli sonuçları şunlardır:STZ uygulanan gruplarda DN yapabilecek ölçüde hiperglisemi gelişmiştir. Nöropati için gerekli süre tamamlanmıştır.Düşük doz (0,3mg/kg) NT-4 uygulanan grupta ağrı eşiği değerleri diyabetik kontrol ve sağlıklı kontrol grupları ile farklılık göstermemiştir.Yüksek doz (3mg/kg) NT-4 uygulanan grupta hot plate ağrı eşiği değerlerinde sağlıklı kontrol grubu, diyabetik kontrol grubu ve düşük doz uygulanan gruplara göre artış gözlenmiş olup, bu artış yüksek doz NT-4 uygulanan grupta istatistiksel olarak anlamlılık düzeylerine ulaşmıştır (p<0,05).

Investigation of Effects of Neurotrophic Factors on Painful Neuropathic PainDiabetes mellitus is characterized by chronic hyperglycemia with disturbances of carbohydrate, fat, and protein metabolism resulting from defect in insulin secretion, insulin action or both.In this study, we have studied the effects of neurotrophin-4 different doses, on the pain treshold levels of diabetic mouses induced with streptozosin.Thirty five number three-week olds male rats were used. Following the induction in the rats which were induced diabetes with STZ ( nearly 4 weeks ) ; diabetic animals were divided into sub-groups. The first group healthy control group ( n=15 ), the second group diabetic control group ( n=10 ) , the third group the group to which low dose (0.3 mg/ kg ) recombinant human NT-4 will be applied group and the fourth group the group to which high dose recombinant human NT-4 will be applied ( n =6 ) were constituted from rats.As a result in this study, in the rats which were made diabetes with STZ hot plate test was applied with the purpose of analysing the effects of neurotrophic factors on painful diabetic neuropathy and the important results of the study are :In the groups which were applied STZ hyperglycemia formed at a rate which can cause diabetic neurophaty. The required time for neuropathy was completed.In the low dose (0.,3/kg) NT-4 applied group, the values of pain threshold differed from diabetic control group and healthy control groupIn the high dose (0.,3/kg) NT-4 applied group , a rise was observed in the pain threshold values of hot plate in comparison with the healthy control group ,diabetic control group and low dose applied group and this rise reached at the level of significance statistically in the group whic was applied high dose NT-4.
Investigation of effects of neurotrophic factors on painful neuropathic pain
Keywords: Endokrinoloji ve Metabolizma Hastalıkları